Isolation and Characterization of Highly Pure Type A Spermatogonia From Sterlet (Acipenser ruthenus) Using Flow-Cytometric Cell Sorting - Xie, Xuan; Tichopád, Tomáš; Kislik, Galina; Langerová, Lucie; Abaffy, Pavel; Šindelka, Radek; Franěk, Roman; Fučíková, Michaela; Steinbach, Christoph; Shah, Mujahid Ali; Šauman, Ivo; Chen, Fan; et al. (Frontiers in Cell and Developmental Biology, 2021)
Sturgeons are among the most ancient linages of actinopterygians. At present, many sturgeon species are critically endangered. Surrogate production could be used as an affordable and a time-efficient method for endangered sturgeons. Our study established a method for identifying and isolating type A spermatogonia from different developmental stages of testes using flow cytometric cell sorting (FCM). Flow cytometric analysis of a whole testicular cell suspension showed several well-distinguished cell populations formed according to different values of light scatter parameters. FCM of these different cell populations was performed directly on glass slides for further immunocytochemistry to identify germ cells. Results showed that the cell population in gate P1 on a flow cytometry plot (with high forward scatter and high side scatter parameter values) contains the highest amount of type A spermatogonia. The sorted cell populations were characterized by expression profiles of 10 germ cell specific genes. The result confirmed that setting up for the P1 gate could precisely sort type A spermatogonia in all tested testicular developmental stages. The P2 gate, which was with lower forward scatter and side scatter values mostly, contained type B spermatogonia at a later maturing stage. Moreover, expressions of plzf, dnd, boule, and kitr were significantly higher in type A spermatogonia than in later developed germ cells. In addition, plzf was firstly found as a reliable marker to identify type A spermatogonia, which filled the gap of identification of spermatogonial stem cells in sterlet. It is expected to increase the efficiency of germ stem cell culture and transplantation with plzf identification. Our study thus first addressed a phenotypic characterization of a pure type A spermatogonia population in sterlet. FCM strategy can improve the production of sturgeons with surrogate broodstock and further the analysis of the cellular and molecular mechanisms of sturgeon germ cell development.